Pengaruh tingkat pengetahuan dan sikap tentang pacaran terhadap perilaku pacaran pada siswa SMA di Yogyakarta - Meilani, Niken; Setiyawati, Nanik (Poltekkes Kemenkes Yogyakarta, 2017)
Adolescence was a period of transition from childhood to adulthood and developmental changes, whether physical, mental, or socialrole. Premarital sex behavior was a serious problem that was the most important risk factor for the incidence of disability and death.Dating was a close relationship between men and women who were at risk of physical contact and even end up with premarital sex.This study aims to determine the effect of knowledge level on adolescent reproductive health and adolescent attitudes about datingto dating behavior among high school students. This research was correlational analytic research using survey method. Theapproach used was cross sectional. The research was conducted in six senior high school in Yogyakarta which was chosen byrandom number of 370 respondents. Data collection tool using questionnaire. The results of this study showed that 68.1% ofrespondents are female, 58.6% of respondents have a good level of knowledge, 38.4% of respondents have a disagreement attitudeof dating, 18.9% was dating and 55.7% dating without physical contact. Bivariate analysis showed that knowledge level (p=0.14) andattitude (p=0.000) were related to dating behavior. Multivariate analysis showed attitude toward dating effect on dating behavior(p=0.10, OR=2.9). It is very necessary to provide mentoring to the teenagers either in the form of information or mentoring so thatteens can have a positive attitude to avoid dating.